Sequencing and characterization of the complete mitochondrial genomes of three Pneumocystis species provide new insights into divergence between human and rodent Pneumocystis. Issue 5 (7th February 2013) - Ma, Liang; Huang, Da‐Wei; Cuomo, Christina A.; Sykes, Sean; Fantoni, Giovanna; Das, Biswajit; Sherman, Brad T.; Yang, Jun; Huber, Charles; Xia, Yun; Davey, Emma; Kutty, Geetha; et al.
Abstract : Pneumocystis jirovecii is an important opportunistic pathogen associated with AIDS and other immunodeficient conditions. Currently, very little is known about its nuclear and mitochondrial genomes. In this study, we sequenced the complete mitochondrial genome (mtDNA) of this organism and its closely related species Pneumocystis carinii and Pneumocystis murina by a combination of sequencing technologies. Our study shows that P. carinii and P. murina mtDNA share a nearly identical number and order of genes in a linear configuration, whereas P. jirovecii has a circular mtDNA containing nearly the same set of genes but in a different order. Detailed studies of the mtDNA terminal structures of P. murina and P. carinii suggest a unique replication mechanism for linear mtDNA. Phylogenetic analysis supports a close association of Pneumocystis species with Taphrina, Saitoella, and Schizosaccharomyces, and divergence within Pneumocystis species, with P. murina and P. carinii being more closely related to each other than either is to P. jirovecii. Comparative analysis of four complete P. jirovecii mtDNA sequences in this study and previously reported mtDNA sequences for diagnosing and genotyping suggests that the current diagnostic and typing methods can be improved using the complete mtDNA data. The availability of the complete P. jirovecii mtDNA also opens the possibility of identifying new therapeutic targets.—Ma, L., Huang, D. W., Cuomo, C. A., Sykes, S., Fantoni, G., Das, B., Sherman, B. T., Yang, J., Huber, C., Xia, Y., Davey, E., Kutty, G., Bishop, L., Sassi, M., Lempicki, R. A., Kovacs, J. A. Sequencing and characterization of the complete mitochondrial genomes of three Pneumocystis species provide new insights into divergence between human and rodent Pneumocystis . FASEB J. 27, 1962–1972 (2013). www.fasebj.org